Metabolic changes to GLUT-4 levels in urban Chacma baboons on the Cape Peninsula: raiding their way to type 2 diabetes? - Van Velden, Julia (Department of Biological Sciences, 2014)
The Chacma baboons (Papio ursinus) of the Cape Peninsula are established raiders of human food, leading to widespread conflict between this intelligent, adaptable species and humans. The modern Western diet that these baboons have become exposed to has many deleterious effects on health, including obesity and type 2 diabetes. The aim of this study was to investigate whether this population of baboons have lowered GLUT-‐4 transporter protein levels in comparison to wild-‐feeding baboons, as an indication of insulin abnormalities. GLUT-‐4 levels were analysed via Western Blot and DXA scanning was used to compare physical characteristics between these two groups. No significant difference in GLUT-‐4 levels was found, however the two groups differed in three physical variables, with the semi-‐provisioned Peninsula group having higher total weight (kg)(p<0,05), total body lean mass (kg) (p<0,01) and bone mineral content (kg)(p<0,001) than the wild-‐feeding controls. These results indicate that male individuals from the Peninsula population are bigger but not fatter than wild-‐feeding male baboons from the Eastern Cape population. Although it could not be determined whether human food is causing insulin abnormalities in the Cape Peninsula’s population of Chacma baboons, this study indicates that this is a promising area of research, likely to affect the management strategies used on this population.